The influence of Environment and Parasitism on the prevalence of Asthma in two Venezuelan regions - Perdomo de Ponce, Doris; Benarroch, Lorena; Aldrey, Oscar; Rodríguez, Dalila; Rosales, Anselmo; ívila, Emilio; Bianco, Nicolas (Investigación Clínica, 2013)
The point prevalence of bronchial asthma and the influence of environmental conditions among 100 individuals chosen from two Venezuelan regions, i.e., rural and urbano were investigated by history, routine laboratory tests, determination of total and specific IgE antibody to common allergens and spirometric tests. The point prevalence of bronchial asthma was 3,0% in rural subjects who were also highly parasitized by helminths and 3,6% in subjects from the urban region. A significative difference in skin responses to Dermatophagoides pteronnysinus was observed in urban asthmatics when compared with rural asthmatics. A similar response to selected allergens was found among both populations. The prevalence of infestation by Ascaris in rural asthmatics was high compared with that of rural controls. Total IgE levels were elevated for both populations, but significatively higher (p < 0.05) for rural individuals. Results suggest a significative point prevalence of bronchial asthma in both regions, despite the helminth infestation of rural subjects. The effects of environmental factors, their concentration and time of exposure are considered as main factors responsible for allergic reactivity observed in the Venezuelan regions studied.